2015
DOI: 10.1002/ejic.201403037
|View full text |Cite
|
Sign up to set email alerts
|

A Fivefold Interpenetrating dmd Topological Copper(I) Cyanide Complex Formed by C–C Bond Cleavage of Acetonitrile

Abstract: The solvothermal reaction of a mixture of copper nitrate and 3,5‐bis(4‐pyridyl)‐1H‐1,2,4‐triazole (4,4′‐Hbpt) in a mixed acetonitrile/water solvent leads to a special copper(I) cyanide complex Cu3(CN)3(4,4′‐Hbpt)2 (1) with a fivefold interpenetrating dmd topological framework. The cyanide ligands in the structure are generated in situ from the C–C cleavage of acetonitrile under solvothermal conditions. Solid‐state luminescence experiments show that 1 can emit efficient violet luminescence, and the possible emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…[24] The Ag-O bond lengths vary from 2.299(2) to 2.555(2) Å and the Ag-N distance is 2.227(2) Å. The bond angles around Ag are in the range of 90.14 (7) to 127.41(8)°, which are within the limits of corresponding parameters found in the literature. [25] The rigid carboxyl groups of muco 2ligands are fully deprotonated with the unprecedented μ 6 -η 2 :η 1 :η 2 :η 1 bridging coordination mode by connecting six central Ag I atoms.…”
Section: Crystal Structure Of [Ag 2 (Btb)(muco)] N (2)supporting
confidence: 77%
See 2 more Smart Citations
“…[24] The Ag-O bond lengths vary from 2.299(2) to 2.555(2) Å and the Ag-N distance is 2.227(2) Å. The bond angles around Ag are in the range of 90.14 (7) to 127.41(8)°, which are within the limits of corresponding parameters found in the literature. [25] The rigid carboxyl groups of muco 2ligands are fully deprotonated with the unprecedented μ 6 -η 2 :η 1 :η 2 :η 1 bridging coordination mode by connecting six central Ag I atoms.…”
Section: Crystal Structure Of [Ag 2 (Btb)(muco)] N (2)supporting
confidence: 77%
“…In particular, the cyanide group is a versatile ligand that can act as monodentate ligand as well as μ 2 ‐bridging ligand to generate intriguing topological architectures. A few recent reports shown that the special Cu complexes can be used to cleave the C–C bond of acetonitrile molecules into cyanide anions mainly under hydrothermal/solvothermal conditions 7,8. On the other hand, the organic dicarboxylate ligands can exhibit diverse coordination modes, high thermal stability, and strong coordination ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Cu(I) cyanide complexes have received wide recognition for their unique physical and chemical properties, in which Cu(I) favors trigonal or tetrahedral coordination in the presence of cyanide groups. These cyanide groups offer the possibility of promoting the formation of frameworks because of their strong coordinating nature [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…12 As it was mentioned at the beginning, activation of C-C bonds by transition metal complexes in homogeneous media is a constant area of research in organometallic chemistry. [23][24][25][26][27][28] In this context, it has recently been found the Ag(I)-mediated formation of a 2D cyano-bridged multinuclear Ag(I) alkynyl network formed throught the C-C bond cleavage of acetonitrile that is acting as source of CNions. 30 S45-S47 in the ESI).…”
mentioning
confidence: 99%